Pengaruh Budaya Organisasi dan Kompetensi terhadap Kinerja Karyawan PT. Bratachem Indonesia - Laia, Rispan Syah Putra; Siregar, Dahrul (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of organizational culture and competence on employee performance at PT. Bratachem Indonesia Medan. The background of this research is based on the phenomenon of delays in task completion, low adherence to work norms, and the lack of optimal communication and analytical skills among some employees. This research employs a quantitative approach with a descriptive-associative method. The population consists of all permanent employees of PT. Bratachem Indonesia, totaling 69 respondents, selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 23. The results show that organizational culture has a positive and significant effect on employee performance with a regression coefficient of 0.322, while competence also has a positive and significant effect with a regression coefficient of 0.588. The simultaneous test (F-test) resulted in an F-value of 112.809, which is greater than the F-table value of 3.315 with a significance level of 0.000, indicating that organizational culture and competence together significantly affect employee performance. The coefficient of determination (R²) of 0.773 indicates that 77.3% of the variation in employee performance can be explained by organizational culture and competence, while the remaining 22.7% is influenced by other factors outside this study. These findings confirm that a strong organizational culture and adequate competence are essential factors in improving employee performance. Therefore, the company is advised to strengthen productive work culture values while developing training and mentoring programs that can enhance employee competence.